First order differential equation subordination associated with cassini curve - Andy Liew Pik Hern; Rashidah Omar; Aini Janteng (Hindawi Limited, 2021)
We denote p(z) as analytic functions defined on the open unit disk with p(0) = 1. In this paper, we determined the condition for so that the results hold for the expressions 1+ zp′(z), 1+ zp′(z)/p(z) and 1+ zp′(z)/p2(z) are subordinate to √1 + cz.